2010
DOI: 10.1155/2010/317525
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of a reconstituted myelin sheath

Abstract: Abstract. Myelin is a multilamellar membrane which, wrapping the nerve axons, increases the efficiency of nervous signal transmission. Indeed, the molecular components of the myelin sheath interact tightly with each other and molecules on the axonal surface to drive myelination, to keep both myelin and the axon intact, and to transduce signals from myelin to the axon and vice versa. Myelin is strongly affected in human demyelinating diseases in both the central and peripheral nervous system (CNS and PNS, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Left: the C-shaped particle seen in electron microscopy of MBP bound to lipid monolayers [24]. [48]. The structures are shown on the same scale, and the maximal dimension of MBP in each case is indicated.…”
Section: Basic Proteins Of Myelinmentioning
confidence: 99%
See 1 more Smart Citation
“…Left: the C-shaped particle seen in electron microscopy of MBP bound to lipid monolayers [24]. [48]. The structures are shown on the same scale, and the maximal dimension of MBP in each case is indicated.…”
Section: Basic Proteins Of Myelinmentioning
confidence: 99%
“…The palmitate molecule bound to P2 in the crystal structure is also shown (blue). [48]. A predicted model, using the OPM server [27], for the binding of P2 onto one membrane surface can be seen in Fig.…”
Section: Basic Proteins Of Myelinmentioning
confidence: 99%
“…Previous neutron scattering studies have shown that P2 bound to myelinmimicking vesicles made either of 1,2-dimyristoyl-snglycero-3-phosphatidic acid (DMPA) or of a binary mixture of 1,2-dioleoyl-sn-glycero-3-phospho-L-serine (DOPS) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), respectively, reduces the lipid dynamics [13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used the peripheral membrane protein P2 from the PNS myelin major dense line as a model system to study myelin-like membrane stack formation and structure. P2 interacts with lipid bilayers with high affinity 13,15,5658 . We explored its membrane binding characteristics, determinants, and dynamics more closely.…”
Section: Resultsmentioning
confidence: 99%
“…Upon the formation of a P2-membrane complex, the dynamics of both the protein and lipid components are altered. When bound to P2, the dynamics of the lipid membrane are decreased 56 , while P2 becomes extremely heat-stable when bound to membranes 15 . These observations are likely to be linked to the synergistic effects of P2 and the lipids in the tightening of the 3D molecular assembly, as shown by X-ray diffraction from myelin-mimicking bicelle complexes.…”
Section: Discussionmentioning
confidence: 99%